Microbiological quality and sensory evaluation of partially dried mango for fruit salad, Kerabu Mangga - Nizam L.M.; Ardawati A.N.; Nurmahani M.M.; Roshita I.; Zaiton H. (Asian Journal of Agriculture and Biology, 2024)
Indexed by WOS/SCOPUS